Rhythms under tension: Circadian clocks in an Unsynced Society - Aila Akosua Kattner (Biomedical Journal)
This special issue of the Biomedical Journal centers on circadian rhythms, examining the molecular mechanisms of the circadian clock, the consequences of circadian disruption, and their implications for health and disease. Featured topics include blue light therapy for sleep disorders in myocardial infarction patients; sex-specific links between clock genes and colorectal cancer; the impact of social jetlag on blood pressure; and how irregular light-dark cycles and misaligned eating patterns affect circadian stability. A study on Stenabolic (SR9009) in mice investigates its potential to mitigate weight gain, insulin resistance, and white fat accumulation under constant light exposure. Additional reviews address the role of purinoreceptors in extracellular vesicle-mediated communication, the evolving understanding of pseudogenes and their functional derivatives, and future prospects for hyperpolarized magnetic resonance imaging. Original research highlights the influence of corticosterone on white adipose tissue expansion in mice and challenges the assumed protective role of pentoxifylline against diabetic retinopathy in patients with chronic kidney disease and diabetes. A novel application of peripheral magnetic stimulation as a treatment for overactive bladder is also explored. Two studies on hidradenitis suppurativa are included: one linking the condition to an increased risk of migraine in women, and another examining its association with alopecia areata. The issue concludes with two letters to the editor on the effects of the SARS-CoV-2 spike protein on erythrocyte biology, along with a request for further clarification, which is addressed in detail.